Development of improved strain in species of Pleurotus by gamma irradiation - K R, Jyothi (Mushroom Research, 2020)
The oyster mushroom (Pleurotus spp.) is the second important edible mushroom in the world, with 19 per cent contribution to total mushroom production (Sharma et al., 2017). The cultivated mushrooms face the problems like loss of genetic diversity and strain degeneration (Wang et al., 2012). Thus to enhance the productivity and other quality traits, three species of Pleurotus viz., Pleurotus djamor, Pleurotus florida and Pleurotus ostreatus were gamma irradiated at 20 and 25 Gy at 9.779 kGy h-1. Biological efficiency (BE) of P. djamor was increased by 9.25 per cent when the mycelia were irradiated at 20 Gy. The number of days taken for primordial initiation was also reduced by one day compared to P. djamor. Though P. florida irradiated at 25 Gy recorded increase in sporocarp size, there was no significant difference in the BE over P. florida. The BE of P. ostreatus irradiated at 25 Gy was improved by 12.89 per cent and there was earliness in primordial initiation by three days compared to P. ostreatus. The polymorphism per cent was analysed by Random Amplified Polymorphic DNA (RAPD) and revealed that P. djamor, P. florida and P. ostreatus had 16.70%, 25% and 22% polymorphism with their respective improved strains.